2004
DOI: 10.1002/jlcr.852
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of [99mTc(H2O)3(CO)3]+ precursor synthesized by conventional method and by using carbonyl kit

Abstract: SummaryA comparison of the preparation of Tc carbonyl complexes of a few ligands of interest through the conventional method as well as by using the recently introduced carbonyl kit method is described. was also synthesized by using the carbonyl kit and its utility for the synthesis of tricarbonyl complexes was studied by carrying out synthesis of complexes with the above ligands. For comparison, these complexes were first prepared under similar conditions optimized with conventional precursor in order to see … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…In the 99m Tc-MIBI complex, 99m Tc(I) is a soft metal and is complexed by six soft isonitrile ligands in a hexavalent fashion to form a stable octahedral complex [42]. The metal center of [ 99m Tc][Tc(CO) 3 (H 2 O) 3 ] + is likewise soft and the isonitrile ligands can strongly coordinate with it in a 3:1 ratio, as reported previously [43][44][45]. Isonitrile derivatives of arginine-glycine-aspartate (RGD) and nitroimidazole were labeled with 99m Tc by inducing a reaction with [ 99m Tc][Tc(CO) 3 (H 2 O) 3 ] + and have been evaluated in vivo with promising results [38,46].…”
Section: Introductionsupporting
confidence: 58%
“…In the 99m Tc-MIBI complex, 99m Tc(I) is a soft metal and is complexed by six soft isonitrile ligands in a hexavalent fashion to form a stable octahedral complex [42]. The metal center of [ 99m Tc][Tc(CO) 3 (H 2 O) 3 ] + is likewise soft and the isonitrile ligands can strongly coordinate with it in a 3:1 ratio, as reported previously [43][44][45]. Isonitrile derivatives of arginine-glycine-aspartate (RGD) and nitroimidazole were labeled with 99m Tc by inducing a reaction with [ 99m Tc][Tc(CO) 3 (H 2 O) 3 ] + and have been evaluated in vivo with promising results [38,46].…”
Section: Introductionsupporting
confidence: 58%
“…Our lower results (19% on average) are probably due to the lower amount of proteins used (1-2 nmol against 3 nmol), the shorter reaction time (30 min against 1 h) and the use of 99m Tc-tricarbonyl obtained from an Isolink 1 kit. Effectively, Satpati et al 26 demonstrated that the kinetics of radiolabelling reaction was significantly lower when 99m Tc-tricarbonyl was produced from Mallinckrodt's kit than from a reducing reaction in the presence of CO gas. Tait et al 12 showed that three residues of histidine had to be incorporated to annexin V to increase the radiochemical yield from 40 to 60%, and six residues were needed to reach 80%.…”
Section: Radiolabelling Assaymentioning
confidence: 99%
“…The recent advances leading to the development of the aqua complex fac -[ 99m Tc(H 2 O) 3 (CO) 3 ] + have stirred a plethora of research utilizing this core for imaging. It is easily prepared from a kit (Isolink, Mallinckrodt Inc.) under aqueous conditions using a boranocarbonate anion as the reducing agent and an in situ CO source. , The three labile water molecules are easily exchanged for suitable chelates in a fac arrangement. Examples of bioconjugates ranging from derivatized amino acids, carbohydrates, peptides, ,, nucleosides, and others ,,, have been investigated to fine-tune the targeting, improve the biodistribution properties, and increase the clearance from blood pools and organs of the resulting radiotracers.…”
Section: Introductionmentioning
confidence: 99%